METHODOLOGY FOR ANALYSING ADOLESCENT PSYCHOLOGY THROUGH LITERARY WORKS (The Journal of Interdisciplinary Human Studies, 2026)
This section examines the theoretical and methodological foundations for the psychological analysis of adolescent characters in literary works. The study integrates perspectives from literary criticism and psychology to outline a comprehensive framework for reading fictional representations of adolescence. The psychoanalytic approach including Freud’s model of personality structure and defence mechanisms is discussed alongside Uzbek scholarship on literary psychologism. The principal devices through which writers render adolescent interiority inner monologue, stream of consciousness, psychological portrait, psychic conflict, psychological parallelism, and retrospective narration are analysed in detail. The article also surveys dialogic and reader-response approaches, drawing on Bakhtin’s theory of polyphony, Holland’s reader-identification thesis, and Bleich’s subjective criticism. The methodology outlined serves as the analytical basis for the psychological examination of adolescent characters in the short stories «Hellados» and «Do’nan.»
Keywords: adolescent psychology; literary psychologism; psychoanalytic approac; inner monologue; stream of consciousness; psychic conflict